2005
DOI: 10.1152/ajpcell.00387.2004
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Arp2/3 complex by N-WASp is required for actin polymerization and contraction in smooth muscle

Abstract: Contractile stimulation has been shown to initiate actin polymerization in smooth muscle tissues, and this actin polymerization is required for active tension development. We evaluated whether neuronal Wiskott-Aldrich syndrome protein (N-WASp)-mediated activation of the actin-related proteins 2 and 3 (Arp2/3) complex regulates actin polymerization and tension development initiated by muscarinic stimulation in canine tracheal smooth muscle tissues. In vitro, the COOH-terminal CA domain of N-WASp acts as an inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
223
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(232 citation statements)
references
References 50 publications
(88 reference statements)
9
223
0
Order By: Relevance
“…For vascular smooth muscle cells, vasoconstrictors and growth factors are common humoral factors that induce changes in tension development by the cytoskeleton through crossbridge cycling and structural remodeling (43, 44, 136, 137, 163). As discussed above, increasing evidence indicates that the contractile process in smooth muscle is accompanied by changes in actin polymerization and the recruitment of structural proteins (including, vinculin, paxillin, talin and ␣-actinin) to the cytoplasmic side of focal adhesion sites (68, 161,165,[180][181][182][183]. It has been shown that these changes strengthen and stiffen the cytoskeleton, increasing the mechanical efficiency of the cell for the transmission of force, while reducing the elasticity of the cell over time.…”
Section: Reviewsmentioning
confidence: 97%
“…For vascular smooth muscle cells, vasoconstrictors and growth factors are common humoral factors that induce changes in tension development by the cytoskeleton through crossbridge cycling and structural remodeling (43, 44, 136, 137, 163). As discussed above, increasing evidence indicates that the contractile process in smooth muscle is accompanied by changes in actin polymerization and the recruitment of structural proteins (including, vinculin, paxillin, talin and ␣-actinin) to the cytoplasmic side of focal adhesion sites (68, 161,165,[180][181][182][183]. It has been shown that these changes strengthen and stiffen the cytoskeleton, increasing the mechanical efficiency of the cell for the transmission of force, while reducing the elasticity of the cell over time.…”
Section: Reviewsmentioning
confidence: 97%
“…Contractile agonists have been shown to stimulate actin polymerization in a number of smooth muscle cells and tissues, and the critical role of actin polymerization in regulating active tension development in smooth muscle is well documented (4,8,12,16,18,22,29,38,63,64,67). The inhibition of actin polymerization using either pharmacologic or molecular approaches has been shown to depress tension development in many smooth muscles with little or no effect on MLC phosphorylation or cross-bridge cycling (16, 38, 42, 43, 49, 51, 57-59, 64, 65).…”
mentioning
confidence: 99%
“…Previous studies on animal models have shown an involvement of the N‐WASP protein from the WASL gene in the regulation of actin polymerization and contractility in smooth muscle of mammalian airways,36 but effects on aortic stiffness have not been determined. Thus, N‐WASP was an attractive candidate molecule to pursue with a decoy peptide strategy to determine effects on stiffness.…”
Section: Resultsmentioning
confidence: 99%
“…The CA domain of N‐WASP is a subset of the C‐terminal VCA domain by which N‐WASP activates the Arp 2/3 complex, inducing actin polymerization at branches from the side of parent actin filaments 36, 37. The CA domain binds to G‐actin, and because it lacks the V domain, acts as a dominant negative inhibitor of N‐WASP‐mediated actin polymerization in airway smooth muscle,36 but its effects in vascular smooth muscle are unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation